Insight into Noninvasive Radiological Modalities to Detect Heart Transplant Rejection - Sharma, Dhruva; Subramaniam, Ganapathy; Sharma, Neha; Sharma, Preksha; Sharma, Pooja (Indian Journal of Radiology and Imaging, 2021)
Purpose Patients with end-stage heart failure who remain symptomatic even with exemplary medical and device therapy are treated with heart transplantation. Multitudes of endeavor have been contrived during the last decennium in the field of noninvasive tests to rule out heart transplant rejection (HTR). In spite of having supportive literature, noninvasive imaging techniques lack acceptable documentation of clinical robustness, and endomyocardial biopsy (EMB) still remains the gold standard. The aim of this review is to shed light on the existing noninvasive radiological modalities to detect rejection among heart transplant recipients.Methods A comprehensive search was conducted for this review article on the basis of literature available including scientific databases of PubMed, Embase, and Google Scholar, using keywords of “Heart transplantation,” “Acute allograft rejection,” “Arrhythmias,” “Echocardiography,” “Speckle tracking echocardiography,” and “Cardiac magnetic resonance imaging” from inception until September 2020.Results After preliminary screening of the databases, details regarding existent noninvasive radiological modalities to detect HTR were gathered and compiled in this review article. Currently, deformation imaging using speckle tracking and T2 time using cardiac magnetic resonance imaging can serve as screening tools based on which further invasive investigations can be planned. Standardization of blood-based and imaging modalities as screening and possible diagnostic tools for rejection would have obvious clinical and financial benefits in the care of growing number of post heart transplant recipients in our country.Conclusion Diagnosis of allograft rejection in heart transplant recipients through noninvasive techniques is demanding. To unravel the potential of noninvasive radiological modalities that can serve as a standard-of-care test, a prospective multicentric study randomizing noninvasive modality as first strategy versus current EMB-based gold standard of care is the need of the hour.
Keywords: acute allograft rejection; cardiac magnetic resonance imaging; echocardiography; heart transplantation; speckle-tracking echocardiography